On-demand energy flexibility market via smart contracts to help reduce balancing costs in Great Britain - Savelli, I; Bokkisam, HR; Cuffe, P; Morstyn, T (Elsevier, 2023)
The large deployment of renewable generation required to reach net-zero carbon emission requires significant investments in transmission network infrastructure to reduce grid congestion, as well as costly investments in dispatchable assets to manage the intermittency of renewable energy. The provision of flexibility services to system operators represents an additional method that could help solve these issues. However, this requires the engagement of a large number of small users, such as households and small commercial firms, that usually cannot directly participate in electricity markets due to their limited size. Blockchain technologies leveraging smart contracts can provide an autonomous, cost-saving and transparent tool to help engage these users in the provision of flexibility services to the grid. The aim of this paper is to design a new market layer for the on-demand provision of flexibility services by using smart contracts fully integrated with existing national-scale electricity markets. We demonstrate how this model can co-exist with the current electricity market architecture in Great Britain (GB), providing a whole-system least-cost solution to solve grid congestion and energy imbalances. Simulations based on a high-fidelity network of GB highlight the potential benefit that the proposed approach could create at the national scale.